SCREENING OF ORNAMENTAL ANNUALS TO THE ROOT KNOT NEMATODE, MELOIDOGYNE INCOGNITA, IN IRAQ - QAMAR MAJEED, J. P. SINGH* AND (Indian Phytopathology, 2002)
Root-knot nematode is a major factor limiting production of ornamental annuals in Iraq. About 50 commonly grown flowering annuals belonging to 20 different families were evaluated for their reaction to root-knot" nematode, Meloidogyne incognito, in replicated trials under the field and pot conditions. Investigations revealed that 30 per cent annuals did not show infestation at all and rated as resistant; 26 per cent yielded infestation in pots only while 44 per cent developed infestation under both conditions. These 30 per cent annuals would serve as a valuable materials to breeders interested in developing nematode resistant varieties of ornamental annuals. The results further suggest that susceptible annuals be rotated with resistant ones and should not be planted in the same piece of land year after year.